Mining for Cryptocurrencies, Extracting from Communities? A Case Study of Belvoir - Ihuka, Victor Chimaihe (East Carolina University)
Hundreds of studies conclude that, generally, ethnic minorities, indigenous persons, people of color, and low-income communities confront a higher burden of environmental exposure from air, water, and soil pollution from industrial facilities. This is due to entrenched segregation, racially motivated decisions in the zoning ordinances, eminent domain, (lack of) government regulations, and urban renewal. However, most Environmental Justice research has focused on proximity to hazardous waste sites and facilities (landfills, incinerators, superfund sites, etc.) In the Fall of 2021, Compute North (a Minnesota-based technology firm) sought a special use permit to operate a cryptocurrency mining facility in Belvoir, Pitt County. The project prompted protests when it became clear the proposed site was close to an elementary school in the predominantly Hispanic and African American community. This case study examined what aspects of (or lack thereof) of the proposal for Compute North to build a crypto-currency facility in Pitt County that reflected transparency; how community members were able to participate in the process and if this participation full and equitable, and lastly, the case study examined community members' perceptions of fairness regarding their participation and access to support and information during this process. Cryptocurrency has gained significant attention in recent years as a decentralized digital currency that uses cryptography to secure transactions and control the creation of new units. Crypto-mining and blockchain are relatively new technologies that hold promise for the future of digital finance and the internet of things (IoT). Even though cryptocurrency is a virtual currency, its production is not done in isolation. Cryptocurrency has spatial and social implications for the communities where mining occurs. Some studies have explored the energy consumption and carbon emissions of cryptocurrency mining. The noise pollution associated with crypto mining is also an emerging environmental justice issue. There is also concern about the slew of electronic wastes created by the specialized hardware required to mine crypto. One key area that has not gotten any attention in academic scholarship is the environmental justice dimensions of crypto-mining facilities siting. Using the theoretical frameworks of procedural justice, I analyzed the primary and secondary data (interviews, news articles, minutes of public hearings, etc.) through the lens of narrative analysis to identify themes and patterns within the stories and to understand the social and cultural context in which the stories are situated. The case study serves as a potent reminder of the need for continued vigilance and activism to ensure that all communities, regardless of race, have equal access to environmental benefits and protections. It also underscores the importance of ensuring that these communities are genuinely empowered with the necessary resources, information, and support to contribute meaningfully to environmental decision-making.
Keywords: Zoning; Procedural Justice; Cryptocurrencies--Social aspects--North Carolina--Pitt County; Electronic funds transfers--North Carolina--Pitt County; Environmental justice--North Carolina--Pitt County; Land use, Rural--North Carolina--Pitt County; Noise pollution--North Carolina--Pitt County